Medication-related osteonecrosis of the jaw - Heliton Spindola Antunes; Rogerio Jardim Caldas; Fabiana Caramori Noal Granzotto; Geisa Badauy Lauria da Silva; Walmir Mello; Paulo Sérgio da Silva Santos (Associação Brasileira de Odontologia, 2018)
.